SAT0266 Obesity is Associated with Lower Probability of Achieving Sustained Minimal Disease Activity State Among Patients with Psoriatic Arthritis. (23rd January 2014) - Eder, L.; Thavaneswaran, A.; Chandran, V.; Cook, R.; Gladman, D. D.
Abstract : Background: The prevalence of obesity among patients with psoriatic arthritis (PsA) is increased compared to the general population. Obese patients with PsA tend to respond less favorably to TNF alpha blockers compared to patients with normal weight. Objectives: To investigate the association between obesity and outcome of the disease in patients with PsA by assessing if overweight and obese patients are less likely to achieve sustained minimal disease activity (MDA) state. Methods: A cohort analysis of patients followed prospectively from 2003 to 2012 at a large PsA clinic was performed. Patients were scheduled to be followed at 6-12 month intervals according to a standard protocol. Demographic, clinical, laboratory and radiographic data were entered into a computerized database. Patients with a follow-up of less than 1 year were excluded. Body Mass Index (BMI) was calculated and patients categorized accordingly into the following groups: Normal (<25), Overweight (25-30) and Obese (>30). Sustained MDA was defined as fulfilling at least 5 out of 7 criteria as suggested by Coates et al [1] for at least 1 year. Proportional odds discrete time to event analysis was used to investigate the association between BMI category and the achievement of sustained MDA, adjusting for age, gender, disease duration, DMARD and TNF alpha blocker use. Results: A total of 557 patients (58.7% males) were included in the study. Their mean age and disease duration at baseline were 48.6±13.1 and 11.5±10.4 years, respectively. 36.2% of the patients were classified as overweight and 35.4% were obese. Overall, 66.1% of the patients achieved sustained MDA. High HAQ and pain scores were the items that most frequently prevented patients from achieving MDA. Overweight and obese patients were older at baseline (p=0.04) and were older at onset of PsA (p=0.002) and psoriasis (p=0.002). They were also more likely to use NSAIDs (p=0.005) compared to patients with normal weight. A dose response association was found between obesity and the probability of achieving sustained MDA in the multivariate regression analysis. Patients in the higher BMI categories were less likely to achieve sustained MDA compared to patients in the lower BMI category (BMI 25-30: Odds Ratio (OR) 0.64 p=0.001, BMI>30: OR 0.52 p<0.0001) after adjusting for potential confounding variables. Conclusions: The prevalence of obesity and overweight is high in patients with PsA. Patients who are overweight and obese are less likely to achieve sustained MDA compared to patients with normal weight. References: Coates LC et al. Frequency, predictors, and prognosis of sustained minimal disease activity in an observational psoriatic arthritis cohort. Arthritis Care Res. 2010;62:970-6 Disclosure of Interest: None Declared